The Role of the Literary and Social Protest in the selected Novels of John Steinbeck in the Global Supply Chain - Rasha Hassooni Abdullah (International Journal of Supply Chain Management, 2018)
Let us rise up tonight with a greater readiness. Let us stand with a greater determination. And let us move on in these powerful days, these days of challenge to make America what it ought to be. We have an opportunity to make America a better nation. (Martin Luther King, Jr.1). The notion of